Vaccines for emerging pathogens: from research to the clinic - Williamson, E. D. (Clin Exp Immunol, 2019)
In this two‐part series of reviews, we have invited experts in their fields to contribute articles on the status of vaccine research and development for emerging pathogens. This topic has been brought into sharp focus in recent years following significant outbreaks of viral diseases such as those causing severe acute respiratory syndrome and Middle East respiratory syndrome, as well as devastating outbreaks of diseases caused by the Ebola, Marburg, Zika and Lassa fever viruses, to name only a few examples. Additionally, bacterial infections leading to bubonic and pneumonic plague, most notably in Madagascar in 2018, as well as malaria in many tropical countries, melioidosis in south east Asia and tularaemia in northern Europe and North America, have incurred significant morbidity and mortality. In this review series, the life cycle of these pathogens and the epidemiology of disease have been reviewed in the context of potential points of intervention for the prevention of human infection. Many of the emerging pathogens are zoonoses and, as such, there is scope for intervention at the animal/insect/environmental reservoir. Other pathogens covered in this review series are considered to be re‐emerging, such as multi‐drug resistant tuberculosis.